The effect of electromagnetic fields on survival and proliferation rate of dental pulp stem cells. (2nd October 2020) - Samiei, Mohammad; Aghazadeh, Zahra; Abdolahinia, Elaheh Dalir; Vahdati, Amin; Daneshvar, Sabalan; Noghani, Atefe
Abstract: Aims: Extremely low-frequency electromagnetic fields (ELF-EMF) can affect biological systems and alter some cell functions like proliferation rate. Dental pulp tissue is known as a source of multipotent stromal stem cells (MSCs), which can be obtained by a less invasive and more available process compared to bone marrow-derived stem cells (BMSCs). This study aimed to consider the effect of ELF-EMF on proliferation rates of human dental pulp stem cells (hDPSCs). Material and methods: ELF-EMF was generated by a system including autotransformer, multi-meter, solenoid coils, teslameter and its probe. The effect of ELF-EMF with the intensity of 0.5 and 1 mT and 50 Hz on the proliferation rate of hDPSCs was assessed in 20 and 40 min per day for 7 days. MTT assay and DAPI test were used to determine the growth and proliferation of DPSCs. Results: Based on MTT, ELF-EMF has maximum effect with the intensity of 1 mT for 20 min/day on the proliferation of hDPSCs. The survival and proliferation rate in all exposure groups were significantly higher than the control group. Based on the data obtained from MTT and DAPI assay, the number of viable cells in the group exposed to 1 mT for 20 min/day was higher than other groups ( p < .05). Conclusions: Regarding to the results of this study, 0.5 and 1 mT ELF-EMF can enhance survival and proliferation rates of hDPSCs.